Imaging of Intracranial Infections - Abdalkader, Mohamad; Xie, Juliana; Cervantes-Arslanian, Anna; Takahashi, Courtney; Mian, Asim Z. (Seminars in Neurology, 2019)
Central nervous system (CNS) infections are a major source of morbidity and mortality despite the remarkable progress in prevention and treatment of infectious disease. Because of the difficulty of direct tissue sampling, imaging plays a crucial role in detecting, diagnosing, and monitoring the therapeutic response of CNS infections. An accurate diagnosis in CNS infections is especially rewarding, given the availability of potential effective antimicrobials.Bacterial, viral, fungal, and parasitic infections may affect the brain and/or its meningeal coverings, and can be characterized by a variety of radiological patterns that help narrow the differential diagnoses and eventually tailor the optimal management.This review addresses the typical imaging findings of intracranial infectious diseases in both immunocompetent and immunocompromised patients.
Keywords: neuroimaging; CNS infections; immunocompetent patients; immunocompromised patients